(untitled) (De la Crítica, 2024)
Reading gives a communicative and linguistic interchange to deaf people. Thus, the purpose of this article was to establish the resources used for the development of reading comprehension in deaf students. To this end, a bibliographic review was carried out, considering a qualitative approach and the selection of 6 articles which were located within digital databases such as Redalyc, Google Academic and Scielo, and taken into account from the application of the inclusion criteria established for this review. Subsequently, it was obtained as a result that the most used resources were technological ones such as the digital book, the virtual learning classroom, the blog, pictograms, Kamishibai and the story, which were used at different educational levels such as primary, secondary and university. All of these technology-mediated resources provide visual support for the development of reading comprehension. It is also concluded that teachers must consider the needs of their students and adapt their activities through the use of technological or traditional resources that allow them to provide motivation and learning in their students.